Analysis of the determinants of education expenditures in Malaysia / Najumunisha Abdul Jabbar & Doris Padmini Selvaratnam - Abdul Jabbar, Najumunisha; Selvaratnam, Doris Padmini (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
Expenditure on education helps in improving the skill formation and raises the ability of individuals to produce and work. It is said to be an investment in human capital which is closely connected with the economic development. Government education spending is of great importance to national development and plays a prime role in assisting growth and knowledge deepening. The aim of this study is to build on the established theories of public policy analysis on education and to empirically investigate and analyze the determinants of public expenditure on education in Malaysia. For the occasion of this study, it is posited that education expenditure is determined by multidimensional determinants. A number of theories are therefore incorporated regarding economic-demographics and political concept which have been used in the study. The results reveal that the education policy in Malaysia is mainly determined by budget deficit and the revenue collected by the government with a significant coefficient variables of -0.22and 0.15 percent respectively. Besides, unemployment has an inverse but insignificant impact on total educational expenditures. These results imply that the Malaysian government mainly takes into account only certain factors and neglect to incorporate the importance of other factors, such as demographic and educational indicators, when allocating education expenditures. Whereas Malaysian government education expenditure doesn’t focus on the political factor which is well described by the insignificant level of 0.80 percent of the dummy election cycle variable.